ANALISIS PERILAKU PENCEGAHAN NARKOTIKA PADA SISWA SMA NEGERI 5 KOTA MAKASSAR - Azwar, Muhammad; Widiastuty, Lilis (UNM Environmental Journals, 2023)
This research aims to analyze drug prevention strategies among students of Senior High School Negeri 5 Makassar. The study employs a descriptive method, involving student samples from various grade levels. Data were obtained through questionnaires and interviews. The research findings indicate that students are inclined to be vulnerable to drug exposure. Contributing factors to this behavior include students' lack of knowledge about the risks of drug abuse, peer pressure, and insufficient supervision from parents and the school. In preventing drug behavior, it was found that an educational approach integrated with strict supervision has a positive impact. Active involvement of parents and teachers in providing information about the dangers of drugs, as well as offering emotional support to students, is also crucial. Therefore, collaborative efforts among the school, parents, and the community are necessary to develop a comprehensive and effective prevention program to safeguard students from the dangers of drugs.